Feasibility Analysis of Layer Chicken Farming Business (Kwarti Toto Pram) In simpang Poak Village Curup Tengah District Rejang Lebong Regency - Marwanti, Rahayu; Yanuarti, Mira; Effendi, Darwan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the financial feasibility of a layer chicken farming business owned by Mr. Kwat Tritoto located in Simpang Poak, Curup Tengah District, Rejang Lebong Regency. Conducted from April to May 2025, this research used a descriptive quantitative approach by collecting primary data through observation, interviews, documentation, and questionnaires. Financial feasibility analysis was performed by calculating total production cost, total revenue, net income, and the Revenue/Cost (R/C) ratio. The result showed that the business is financially feasible, generating a monthly profit of IDR 13,556,460 with an R/C ratio of 1.36.